EVALUASI SIFAT FISIK SEDIAAN FACIAL WASH EKSTRAK ETANOL DAUN SIRIH CINA (Paperomia pellucidaL.)SEDIAAN FACIAL WASH EKSTRAK ETANOL DAUN SIRIH CINA (Paperomia pellucidaL.) - Santika, Maria; Qonitah, Fadilah; Ariastuti, Reni (Melekliterasi Press, 2024)
If dirt on the face is not cleaned over time, it will accumulate into blackheads and pimples. Acne can also occur due to underlying blockage and inflammation, usually caused by the bacteria Propionibacterium acnes. Ethanol extract of Chinese betel leaves contains alkaloids, tannins, lipids and essential oils which have antibacterial properties. The aim of this research is to find out whether the facial wash formulation can meet the requirements for a good physical properties test and to find out whether the Chinese betel leaf extract (Paperomia pellucida L. Kunth) facial wash preparation has inhibitory power against P.acnes. This research is experimental research. Physical property tests carried out include organoleptic, pH, foamability and viscosity tests. Antibacterial activity testing was carried out using the diffusion method. Facial wash preparations from Chinese betel leaf extract (Paperomia pellucida L. Kunth) are made with concentrations of 0% (F0), 10% (F1), 15% (F2), 20% (F3). The results of the antibacterial activity test were tested using one way anova statistics. The research results showed that the facial wash preparation met the requirements for a good physical properties test and there was no significant difference between the formulas. The average results of the positive control antibacterial activity test for clindamycin had an inhibitory power of 19.53 ± 0.38 mm (strong), the facial wash preparation of Chinese betel leaf ethanol extract with a concentration of 10% was 8.90 ± 0.97 mm ( moderate), 15% concentration 12.00 ± 0.24 mm (strong), 20% concentration 13.33 ± 0.38 mm (strong), and negative control 0 ± 0 (not inhibiting. This study can be concluded that facial wash ethanol extract of Chinese betel leaves can inhibit antibacterial activity and the significant value is 0.000 <0.05, which means there is a difference in each concentration with the positive control